Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

I am working on getting the hang of proofs by induction, and I was hoping the community could give me feedback on how to format a proof of this nature:

Let $x > -1$ and $n$ be a positive integer. Prove Bernoulli's inequality: $$ (1+x)^n \ge 1+nx$$


Base Case: For $n=1$, $1+x = 1+x$ so the inequality holds.

Induction Assumption: Assume that for some integer $k\ge1$, $(1+x)^k \ge 1+kx$.

Inductive Step: We must show that $(1+x)^{k+1} \ge 1+(k+1)x$

Proof of Inductive Step: $$\begin{align*} (1+x)^k &\ge 1+kx \\ (1+x)(1+x)^k &\ge (1+x)(1+kx)\\ (1+x)^{k+1} &\ge 1 + (k+1)x + kx^2 \\ 1 + (k+1)x + kx^2 &> 1+(k+1)x \quad (kx^2 >0) \\ \Rightarrow (1+x)^{k+1} &\ge 1 + (k+1)x \qquad \qquad \qquad \square \end{align*}$$

share|cite|improve this question
Thanks for the suggestions, I'll keep your tips in mind. – Moderat Aug 12 '12 at 15:09
Where did you uses $x>-1$? Hint: you did use it. – Thomas Andrews Aug 12 '12 at 15:16
When I claimed that $kx^2 >0$ – Moderat Aug 12 '12 at 15:18
Actually, you need it when you multiply both sides by $1+x$. Also, since $x$ can be 0, $kx^2\ge0$ – Mike Aug 12 '12 at 16:06
Ah thank you @Mike – Moderat Aug 12 '12 at 17:03
up vote 2 down vote accepted

What you have is perfectly acceptable. The calculations could be organized a little more neatly:

$$\begin{align*} (1+x)^{k+1}&=(1+x)(1+x)^k\\ &\ge(1+x)(1+kx)\\ &=1+(k+1)x+kx^2\\ &\ge1+(k+1)x\;, \end{align*}$$

since $kx^2\ge 0$. This completes the induction step.

share|cite|improve this answer

This looks fine to me. Just a small note on formatting of the inequalities: I would combine the third and fourth inequalities as $$ (1+x)^{k+1} \geq 1+(k+1)x+kx^2>1+(k+1)x, $$ so there is no need of the fifth line. Or even $$ (1+x)^{k+1} = (1+x)(1+x)^{k} \geq (1+x)(1+kx)=1+(k+1)x+kx^2>1+(k+1)x. $$

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.